Incidence of Enteric Pathogens and Coliforms in Fish from Domestic Markets of Cochin - A., Surendraraj; Thampuran, Nirmala (Fishery Technology, 2025)
The incidence of human enteric pathogens and other coliforms of dominance in the fish and shellfish from retail markets of Cochin were investigated. Total Enterobacteriaceae count in these samples varied from 2.5 to 6.5 log cfu/g. The generic composition of 248 Enterobacteriaceae isolates showed a dominance of genera Enterobacter, Citrobacter and Escherichia. A small fraction (13.8%) of the E. coli isolates were p haemolytic, but none of them could produce labile toxin when tested by reverse passive latex agglutination (RPLA) method. Other enteric pathogens detected in these samples were Klebsiella, Shigella, Edwardsiella and Arizona. Though they constituted only a minor fraction (14.1%), knowing the established pathogenic potentials of these bacteria in food borne illness, strict adherence to good hygienic practices in retail markets of Cochin is warranted. In the Most Probable Number (MPN) procedure for the detection of total coliforms, faecal coliforms and Escherichia coli along with enteric non-coliform bacteria, oxidase positive Aeromonas spp. interfered by causing positive reaction. The temperature of incubation, pH and bile salt level had a profound effect on lactose fermentation in Brilliant Green Bile Lactose Broth (BGLB) and Elevated Coliform (EC) broth in the MPN procedure. It is found that in the presence of divergent mesophilic flora of tropical conditions, the Ortho Nitro Phenyl b-D-Galactopyranosidase (ONPG) test proved to be more reliable test than lactose fermentation for coliform detection as it alleviated the effect of pH, temperature, etc. on the lactose fermentation.